Facial nerve palsy due to parotid abscess with Warthin's tumor. Issue 3 (2nd May 2017) - Kusunoki, Takeshi; Homma, Hirotomo; Kidokoro, Yoshinobu; Yanai, Aya; Hara, Satoshi; Kobayashi, Yuko; Tou, Miri; Wada, Ryo; Ikeda, Katsuhisa
No abstract available